The Relationship Between Foot Feature Parameters and Postural Stability in Healthy Subjects - Mun, Kyung-Ryoul; Chun, Sungkuk; Hong, Junggi; Kim, Jinwook (SAGE PUBLICATIONS INC, 2019)
Objective: Little has been explored about the disparate contribution of medial longitudinal arch (MLA) and lateral longitudinal arch (LLA) to human gait and postural stability. This study aims to investigate the correlation of foot feature parameters including both MLA and LLA with postural stability. Method: Thirteen young and healthy subjects participated in this study. The newly developed FFMS extracted foot feature parameters in nonweight-bearing (NWB) and weight-bearing (WB) conditions along with postural stability parameters in single-leg-standing (SLS) condition. A bivariate correlation analysis was carried out to investigate the correlation between the foot characteristics and the postural stability parameters. Results: The foot length and width showed negative correlation with center of pressure (CoP) distance in medio-lateral (ML) and total direction, whereas the foot length in NWB and WB conditions, and the foot width in WB condition showed positive correlation with CoP distance in anterior-posterior (AP) direction. The height of the LLA curve and the area of the MLA were correlated with the postural stability parameters in AP direction. The ratios of the LLA height and area showed moderate correlation with the CoP distance in ML direction and total direction. Conclusion: The size of a foot, such as the length and width, is correlated with postural stability. Whereas the MLA features are associated with postural stability in AP direction, the LLA features are associated with that in ML and total direction. Application: The findings suggest that the roles and contributions of the MLA and LLA features in and to the postural control are different.
Keywords: SINGLE-LEG STANCE; LONGITUDINAL-ARCH; GAIT; BALANCE